Biochemical, cytological, and immunological mechanisms of rhododendrol-induced leukoderma. Issue 3 (March 2015) - Tokura, Yoshiki; Fujiyama, Toshiharu; Ikeya, Shigeki; Tatsuno, Kazuki; Aoshima, Masahiro; Kasuya, Akira; Ito, Taisuke
Summary: Recently, an unexpected outbreak of patients with leukoderma occurred in Japan with the use of brightening/lightening cosmetics containing rhododendrol (RD). Patients developed leukoderma mostly on the skin sites repeatedly applied with RD, but some patients also had vitiligo-like lesions on the non-applied sites. RD is a tyrosinase-competitive inhibiting substance, thereby serving as an inhibitor of melanin synthesis. Upon inhibition of tyrosinase, RD is converted to new products such as tyrosinase-catalyzed hydroxyl-metabolite, which damage melanocytes. The melanocyte cell lysates seem to induce T-cell response. The frequencies of CD8 + T cells in both lesional skin and peripheral blood are significantly higher in the RD leukoderma as well as non-segmental vitiligo patients than in normal controls. In HLA-A*02:01 positive cases, circulating Melan-A-specific cytotoxic T cells can be detected at a high frequency. It is thus suggested that RD-induced leukoderma is induced by not only cytolysis of melanocytes but also subsequent immune reactions toward melanocytes.